Association of MHTFR Ala222Val (rs1801133) polymorphism and breast cancer susceptibility: An update meta-analysis based on 51 research studies - Yu, Liwa (BioMed Central, 2012)
BACKGROUND: The association between MHTFR Ala222Val polymorphism and breast cancer (BC) risk are inconclusive. To derive a more precise estimation of the relationship, a systematic review and meta-analysis was performed. METHODS: A comprehensive search was conducted through researching MEDLINE, EMBASE, PubMed, Web of Science, Chinese Biomedical Literature database (CBM) and China National Knowledge Infrastructure (CNKI) databases before August 2012. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to estimate the strength of the association. RESULTS: A total of 51 studies including 20,907 cases and 23,905 controls were involved in this meta-analysis. Overall, significant associations were found between MTHFR Ala222Val polymorphism and BC risk when all studies pooled into the meta-analysis (Ala/Ala vs Val/Val: OR=0.870, 95%CI=0.789–0.958,P=0.005; Ala/Val vs Val/Val: OR=0.895, 95%CI=0.821–0.976, P=0.012; dominant model: OR=0.882, 95%CI=0.808–0.963, P=0.005; and recessive model: OR = 0.944, 95%CI=0.898–0.993, P=0.026; Ala allele vs Val allele: OR = 0.935, 95%CI=0.887–0.986, P=0.013). In the subgroup analysis by ethnicity, the same results were found in Asian populations, while no significant associations were found for all comparison models in other Ethnicity populations. CONCLUSION: In conclusion, our meta-analysis provides the evidence that MTHFR Ala222Val gene polymorphisms contributed to the breast cancer development. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1966146911851976